2019
DOI: 10.1021/acsabm.8b00838
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Controlled Photothermal Assembly of Nanoparticles and Microparticles for Rapid Concentration Measurement of Microbes

Abstract: Light-induced heating on a solid–liquid interface can generate a vapor submillimeter bubble and fluid flow, which enables us to densely and rapidly assemble dispersoids into a desired position (photothermal assembly). Here, we revealed that the surface modulation of the light-induced bubble by a surfactant dominates the assembly dynamics of nanoparticles and microparticles as dispersoids, which results in highly efficient photothermal assembly under the surfactant-controlled fluid flow. This mechanism can faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…(d) Reproduced with permission. [ 85 ] Copyright 2019, American Chemical Society. (e, i) Adapted with permission.…”
Section: Directed Assembly Of Preformed Materialsmentioning
confidence: 99%
“…(d) Reproduced with permission. [ 85 ] Copyright 2019, American Chemical Society. (e, i) Adapted with permission.…”
Section: Directed Assembly Of Preformed Materialsmentioning
confidence: 99%
“…[ 93–95 ] Along with surface assembly of microbes, synthetic particles, and molecules, small‐molecule sensing has been reported based on this phenomenon. [ 96–105 ] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [ 95,106 ] Kim et al.…”
Section: Diffusion‐limit‐breaking Systems For Enhancing Sensor–analytmentioning
confidence: 99%
“…[93][94][95] Along with surface assembly of microbes, synthetic particles, and molecules, small-molecule sensing has been reported based on this phenomenon. [96][97][98][99][100][101][102][103][104][105] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [95,106] Kim et al reported a biphasic liquid system wherein volatile, water-immiscible perfluoropentane (PFP) was emulsified into an aqueous medium as a bubble-generating liquid (Figure 5e).…”
Section: Enhanced Analyte-sensor Contact By Analyte Concentratingmentioning
confidence: 99%
“…On the other hand, paying attention to the collective phenomenon of localized surface plasmons, the principles of light-induced acceleration of the biochemical reactions of biological nanomaterials (e.g., DNA and proteins) were realized based on the synergetic effect of light-induced force and light-induced convection due to photothermal effect 24 27 . In previous studies, “photothermal assembly” based on convection due to photothermal effect and the formation of a submillimeter bubble under local high-temperature conditions were used for large-scale production of organic molecular poly-crystals 28 , electrical detection of bio-nanomaterials 29 , and rapid trapping of microbes at a high density 30 , 31 . As fundamental studies, micron-sized structures have been formed by assembling nanoparticles using a laser-induced microbubble 32 , 33 , and the convection mechanism around the photothermal microbubble has been investigated in detail 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%